2016
DOI: 10.5152/tpd.2016.4351
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Entamoeba gingivalis and Trichomonas tenax in Periodontitis or Gingivitis Patients in Kayseri

Abstract: ÖZAmaç: Bu çalışmada periodontitis ve gingivitis hastalarında E. gingivalis ve T. tenax yaygınlığının araştırılması amaçlanmıştır. Yöntem: Çalışmamıza 107 periodontitis hastası ve 68 gingivitis hastası alınmıştır. Ağzında tespit edilen mevcut mikrobiyal dental plaklar kazınmış ve kazınan plak parçaları, içerisinde % 0,9 serum fizyolojik bulunan tüplere konulmuştur. Örnekler ışık mikroskobu altında incelenmiştir. Ayrıca T. tenax için aynı örnekten bir miktar da besiyerine ekilmiş ve 37°C'de inkübe edilmiştir. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
0
16
0
1
Order By: Relevance
“…To assess the reproducibility of these results, a limited number of studies were found ( Kikuta et al., 1996 ; Trim et al., 2011 ; Bonner et al., 2014 ; Garcia et al., 2018a ; Santi-Rocca, 2020 ; Badri et al., 2021 ; Eslahi et al., 2021 ). The comparisons were further complicated by the reliance of a majority of the previous studies on microscopic detection methods (examination of wet mounts or permanent stained smears) ( Athari et al., 2007 ; Ghabanchi et al., 2010 ; Al-hamiary et al., 2011 ; Ibrahim and Abbas, 2012 ; Yazar et al., 2016 ; Hassan et al., 2019 ). Possible explanations for discrepancy between the results of microscopic detection of oral parasites and the PCR-based results include: the subjectivity of the microscopic approach which depends on the skills and experience of the examiner, the number of the fields examined, the method of microscopy used (light vs. phase-contrast), the use of staining, the nature of mounting media, and the lag time between sampling and examination (particularly for wet mount examination which depends on the viability of oral parasites, since motility is one of the decisive defining features for diagnosis) as discussed previously by ( Bonner et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the reproducibility of these results, a limited number of studies were found ( Kikuta et al., 1996 ; Trim et al., 2011 ; Bonner et al., 2014 ; Garcia et al., 2018a ; Santi-Rocca, 2020 ; Badri et al., 2021 ; Eslahi et al., 2021 ). The comparisons were further complicated by the reliance of a majority of the previous studies on microscopic detection methods (examination of wet mounts or permanent stained smears) ( Athari et al., 2007 ; Ghabanchi et al., 2010 ; Al-hamiary et al., 2011 ; Ibrahim and Abbas, 2012 ; Yazar et al., 2016 ; Hassan et al., 2019 ). Possible explanations for discrepancy between the results of microscopic detection of oral parasites and the PCR-based results include: the subjectivity of the microscopic approach which depends on the skills and experience of the examiner, the number of the fields examined, the method of microscopy used (light vs. phase-contrast), the use of staining, the nature of mounting media, and the lag time between sampling and examination (particularly for wet mount examination which depends on the viability of oral parasites, since motility is one of the decisive defining features for diagnosis) as discussed previously by ( Bonner et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the yet-identified parasitic fraction of the oral microbiome, namely: Entamoeba gingivalis and Trichomonas tenax , is gaining interest as potential contributing factors to the development of periodontal disease ( Marty et al., 2017 ; Bonner et al., 2018 ; Eslahi et al., 2021 ). Several studies aimed to investigate oral colonization by these parasites among healthy individuals and those with periodontal disease with variable results ( Athari et al., 2007 ; Ghabanchi et al., 2010 ; Al-hamiary et al., 2011 ; Trim et al., 2011 ; Ibrahim and Abbas, 2012 ; Bonner et al., 2014 ; Yazar et al., 2016 ; Hassan et al., 2019 ). Such variability can be related to adoption of different approaches for parasite detection, and the existence of previously unknown genetic variants of oral parasites ( Garcia et al., 2018b ; Santi-Rocca, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To assess reproducibility of these results, a limited number of studies were found (34, 36, 43, 53, 54). The comparisons were further complicated by the reliance of a majority of the previous studies on microscopic detection methods (examination of wet mounts or permanent stained smears) (35, 37-41). In the current study, a significant number of colonization cases by the two oral parasites was missed upon using the microscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the parasitic fraction of the oral microbiome, namely: Entamoeba gingivalis and Trichomonas tenax, is considered among the proposed models regarding the contributing factors to the development of periodontal disease (32,33). Several studies aimed to investigate parasitic oral colonization among healthy individuals and those with periodontal disease with remarkably variable results (34)(35)(36)(37)(38)(39)(40)(41). Such variability can be related to adoption of different approaches for parasite detection, the existence of previously unknown genetic variants of oral parasites, in addition to limitations of small sample sizes, and possible bias in selection of study subjects among others as reviewed recently (42,43).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal hastalığa sahip kişilerin biyofilm ve tükrük örneklerinden, E. gingivalis'in sık izole edilmiş olması, bu amibin periodontal hastalıkların etiyolojisinde önemli rol oynadığını düşündürmüştür. Diğer taraftan sağlıklı ağızlarda da bulunabilmesi kommensal bir parazit olarak kabul görmesine neden olmuştur (10)(11)(12)(13) .…”
Section: Periodontal Hastalıkta Entamoeba Gingivalisunclassified